Identification of inositol 1, 4, 5‐trisphosphate‐binding proteins by heparin‐agarose affinity purification and LTQ ORBITRAP MS in Oryza sativa. Issue 20 (19th August 2014) - Nie, Yanli; Huang, Feifei; Dong, Shujun; Li, Lin; Gao, Ping; Zhao, Heping; Wang, Yingdian; Han, Shengcheng
<x xml:space="preserve">Abstract</x> Inositol 1, 4, 5‐trisphosohate (IP3) and its receptors play a pivotal role in calcium signal transduction in mammals. However, no homologs of mammalian IP3 receptors have been found in plants. In this study, we isolated the microsomal fractions from rice cells in suspension culture and further obtained putative IP3‐binding proteins by heparin‐agarose affinity purification. The IP3‐binding activities of these protein fractions were determined by [3H] IP3‐binding assay. SDS‐PAGE and MS analysis were then performed to characterize these proteins. We have identified 297 proteins from the eluates of heparin‐agarose column chromatography, which will provide insight into the IP3 signaling pathways in plants. All MS data have been deposited in the ProteomeXchange with identifier PXD000763 (http://proteomecentral.proteomexchange.org/dataset/PXD000763).